Selenium is a functional component of the female reproductive system. Its role in pregnancy complications - G.K. Sadykova; A.A. Olina (LCC «Medicine-Inform», 2021)
G.K. Sadykova1, A.A. Olina1,2 1Academician E.A. Vagner Perm State Medical University, Perm, Russian Federation 2Ministry of Health of Russian Federation, Moscow, Russian Federation This paper reviews studies on selenium (Se) in human reproduction. Low Se intake is associated with the development of gestational hypertension, miscarriage, premature birth, intrauterine growth restriction, and thyroid gland dysfunction. Therefore, studies on the association between Se deficiency and impaired folliculogenesis, steroidogenesis, and infertility in women are of great interest. Unfortunately, these studies are scarce, and further studies are needed. A significant antioxidant activity of Se-containing enzymes allows for minimizing risks of obstetrical complications associated with placental insufficiency. Therefore, selenium is vital for realizing female reproductive function. However, even given potential risks of insufficient Se-containing product intake, the authors find it unacceptable to recommend Se dotation in the population since toxic effects of Se excess are yet to be fully explored. Further studies on Se biological effects will extend the scope of its u se in obstetrics and gynecology in terms of a preventive approach. Keywords: selenium, placental insufficiency, folliculogenesis, steroidogenesis, antioxidant, miscarriage, premature birth, intrauterine growth restriction. For citation: Sadykova G.K., Olina A.A. Selenium is a functional component of the female reproductive system. Its role in pregnancy complications. Russian Journal of Woman and Child Health. 2021;4(4):328-332 (in Russ.). DOI: 10.32364/2618-8430-2021-4-4-328-332.